KECEMASAN TOKOH DALAM NOVEL ORANG-ORANG BIASA KARYA ANDREA HIRATA - Besdirma Saragih; Maria Matildis Banda; I Ketut Sudewa (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This anxiety of the character in the novel Ordinary People by Andrea Hirata which tells the story of ten friends. The novel Ordinary People was chosen as the research object because this novel contains many lessons and motivations related to friendship. This research aims to analyze: (1) the structure of the novel according to plot, characters and setting. (2) reveals the form of anxiety of the main character in the novel Ordinary People. The theories used in this research are (1) Teeuw's structural theory, and (2) literary psychology theory according to Sigmund Freud. The method used in data collection was library research using reading, listening and note-taking techniques. Then the data was analyzed using qualitative descriptive. The results of this research consist of two parts, namely a structural study and a psychological study. First, the structural study of the novel Orang Ordinary contains three stages of plot in the story and uses a mixed forward (back and forth) plot, namely the initial stage, middle stage and final stage. The anxiety of characters in the novel Ordinary People are divided into two main characters and supporting characters. (1) the main character is Dinah and supporting characters, namely Debut Awaludin, Salud, Sobri, Tohirin, Honorun, Handai, Rusip, Dua Nihe Dan Junilah, Inspector Abdul Rojali, Young Sergeant P. Arbi, Trio Bastardin and Dua Boron, Aini, and Mrs. Desi Mal. The setting of events in the story is divided into three, namely: setting, time and atmosphere. Second, a divided psychological study of literature produces the main character's anxiety which is divided into three, namely realistic anxiety, moral anxiety and neurotic anxiety.